2019
DOI: 10.3390/math7121139
|View full text |Cite
|
Sign up to set email alerts
|

On Jacobi-Type Vector Fields on Riemannian Manifolds

Abstract: In this article, we study Jacobi-type vector fields on Riemannian manifolds. A Killing vector field is a Jacobi-type vector field while the converse is not true, leading to a natural question of finding conditions under which a Jacobi-type vector field is Killing. In this article, we first prove that every Jacobi-type vector field on a compact Riemannian manifold is Killing. Then, we find several necessary and sufficient conditions for a Jacobi-type vector field to be a Killing vector field on non-compact Riem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…[1][2][3]), Jacobi-type vector fields (cf. [4,5]), concircular vector fields (cf. [6][7][8][9]), torse forming vector fields (cf.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]), Jacobi-type vector fields (cf. [4,5]), concircular vector fields (cf. [6][7][8][9]), torse forming vector fields (cf.…”
Section: Introductionmentioning
confidence: 99%
“…In [13], Chen and Deshmukh proved that a complete Riemannian manifold admits a concurrent vector field if and only if it is isometric to a Euclidean space by (1). Similarly, in [14], it has been shown that ( n , g) is isometric to a Euclidean space if and only if ( n , g) permits a nontrivial gradient conformal vector field, that is, a Jacobi-type vector field. On the other hand, Matsuyama [24] derived a characterization stating that if the complete totally real submanifold n for the complex projective space CP n with bounded Ricci curvature admits a function ψ satisfying (3), for λ 1 ≤ n, then n is isometric to the hyperbolic space component that is connected if (∇ψ) x = 0 or if it is isometric to the warped product of a complete Riemannian manifold and the Euclidean line if ∇ψ is nonvanishing, where the warping function θ on R satisfies equation (2).…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…formula (10), along with the fact that ψ = λ 1 ψ, we haveB×{q}Hess(ψ)2 dV = -λ dV -B×{q} Ric(∇ψ, ∇ψ) dV (14). …”
mentioning
confidence: 99%
“…Recently, Al-Dayel et al [6] studied the impact of differential equation (2) on Riemannian manifold (L n , g) by taking the concircular vector field and proved that, under certain conditions, the Riemannian manifold (L n , g) is isometric to Euclidean manifold R n . Similarly, by taking gradient conformal vector field, Chen et al [10] identified that Riemannian manifold (N n , g) is isometric to the Euclidean space R n . However, in [11], it has been proved that the complete totally real submanifold in CP n (complex projective space) with bounded Ricci curvature satisfying (3) is isometric to a special class of hyperbolic space.…”
Section: Introductionmentioning
confidence: 99%